Comparison of twice-daily ranitidine with standard cimetidine treatment of duodenal ulcer. Issue 4 (April 1981) - Walt, R P; Trotman, I F; Frost, R; Golding, P L; Shepherd, T H; Rawlings, J; Hunt, R H; Colin-Jones, D; Milton-Thompson, G J; Misiewicz, J J
Abstract : One hundred and three outpatients with endoscopically diagnosed duodenal ulcer were randomly allocated to treatment with either cimetidine 200 mg tds and 400 mg nocte, or ranitidine 150 mg bd for four weeks. The endoscopists were not aware of the treatment and took no part in the clinical management. On completion of treatment ulcers had healed in 43 of 51 (84%) patients given cimetidine and in 40 of 52 (77%) patients given ranitidine. There were no serious unwanted effects in either treatment group. The results show no significant difference between healing rates after four weeks of standard cimetidine therapy or ranitidine 150 mg bd.